PERAN NOTARIS DALAM AKTA PENGIKATAN GADAI AKIBAT HUKUM WANPRESTASI TERHADAP AKTA PENGIKATAN GADAI DI PT. PEGADAIAN (Persero) DALAM PERSPEKTIF TUJUAN HUKUM - Purwanto Purwanto; Sukarmi Sukarmi (Jurnal Akta, 2017)
This study aims to determine and analyze the role of notary in the process of making pawn bonding deeds in PT. Pegadaian (Persero); knowing and analyzing the consequences of legal wanprestasi against pawn bonding deed in PT. Pegadaian (Persero) in the perspective of law objectives, as well as to describe the solution in overcoming the debtor's default.The method used in this study is the method of normative juridical approach that emphasizes the decomposition and interpretation of data associated with the rules of law or doctrines namely the Book of Civil Law, Government Regulation No. 103 of 2000 on the Public Corporation Pawnshops.The result of this research is that 1) The role of notary in binding process of guarantee of pawn with fidusia notary system does not come into play directly but the product produced by a notary is indispensable, so that later can be used as document to anticipate things unwanted by the parties, by first entering into the mortgage agreement as the principal agreement while the bond agreement binding agreement with the fiduciary system in PT. Pegadaian (Perero) is merely an accesoir agreement of the principal agreement of credit agreement. After the signing of the credit agreement, it is followed by the signing of the guarantee bailing and the delivery of collateral from the debtor to the creditor. However, in the pawn bond agreement with the fiduciary system, the guarantee goods remain controlled by the debtor to be treated, stored and used as well as possible while PT. Pegadaian (Persero) as the creditor only keeps Proof of Ownership of Motor Vehicle owned by debtor, 2) Effect of law of wanprestasi in agreement of pawn binding through fiduciary system in perspective of law objective at PT. Pegadaian (Persero) is that the juridical object of mortgage guarantees is in the power of creditors but because it uses fiduciary system then PT. Pegadaian (Persero) allows the debtor to control the guarantee items to be treated, stored and used, but if the debtor wanpretasi then the PT. Pegadaian (Persero) may confiscate collateral goods from the debtor party but by first sending a warning or a reprimand letter with the criteria approved in the previous credit agreement and 3) Solution to overcome the debtor wanprestasi in pawn bond agreement in fiduciary system at PT. Pegadaian (Persero) then it can be done by checking and visiting the debtor's home to know the condition of the collateral whether it is still in place of the debtor or has been transferred to another party also to know the condition of the last assurance whether it is still as usual or there has been a physical change, which resulting in the selling price down and so forth.Keywords: Notary Role, Default, Deed of Pawn License